Rationalization of wheat markets in Pakistan: Policy options - Rana, Abdul Wajid (International Food Policy Research Institute, 2020)
While wheat procurement policy is a central part of Pakistan’s agricultural policy, a brief description of its impact does not make for easy reading: it has a high budget cost, has led to a buildup of debt, distorts markets, provides little direct benefit to small farmers and productivity in Pakistan’s wheat sector continues to lag. Furthermore, as Pakistan has gradually moved to producing a wheat surplus, a trend that is likely to continue in the future, the current policy set is likely to become more unsustainable in the future, with the task of squaring the circle between supporting farm incomes, providing fair consumer prices and delivering food security becomes increasingly difficult without reform.